An internet of things-based monitoring system for agricultural land suitability for oil palm planting - Amriansyah Simatupang; Mulkan Iskandar Nasution; Muhammad Nuh (Universitas Riau, 2024)
Oil palm is the most productive type of plant in producing vegetable oil. The development of the industrial revolution led to an explosion in demand for vegetable oil so palm oil was a major contributor to the country's foreign exchange. Indonesia is one of the countries with the largest oil palm plantations in the world. However, the yields produced are still not optimal due to several factors, namely the condition of soil pH, soil moisture, and the surrounding temperature. Soil contains nutrients such as nitrogen (N), potassium (K), and phosphorus (P) which oil palm plants need in certain amounts to grow. To find out the quality of the soil, several methods are carried out by taking a soil sample and using a soil pH meter, however, this method requires a long time and the measurement is only limited to measuring soil pH. This research produced a system for detecting soil pH, soil moisture, and temperature around the soil on an IoT-based land that will be planted with oil palm, as the controller is NodeMCU ESP32. This tool displays soil pH, soil moisture, and air temperature on the LCD screen and the Blynk application page so that it can be accessed anytime and anywhere. This will make it easier for oil palm farmers to obtain accurate information before planting oil palm on vacant land. After testing and data collection, the soil pH sensor has a good correlation with an error rate of 1.71%, soil moisture of 1.23%, and air temperature of 4.04%. So that this sensor can be implemented on vacant land before planting oil palm.